Detection of Quantum Cellular Automaton Action in Silicon-on-insulator Cells. Issue 1 (2001) - Gattobigio, M.; Macucci, M.; Iannaccone, G.
Abstract : We present a proposal for an experiment to demonstrate QCA (Quantum Cellular Automaton) functionality for a cell fabricated with silicon-on-insulator technology. The fundamental feature of a working QCA cell consists in the anticorrelated transition of electrons in the two pairs of dots forming the cell: we show how such a phenomenon can be detected from the appearance of a "locking" effect between the Coulomb Blockade current peaks relative to each pair. The proposed approach allows the detection of QCA action without the need for additional noninvasive charge detectors probing each dot. We have performed detailed numerical simulations on the basis of interdot capacitance values obtained from experimental data and determined the range of parameters within which the effect should be detectable.